2016
DOI: 10.5114/aoms.2015.53143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Th1/Th2 cytokine administration on proinflammatory SKOV-3 cell activation

Abstract: IntroductionInterleukin(IL)-1β, IL-6 and IL-12 might associate with inflammatory processes in a tumor progression and create a specific microenvironment for tumor growth. The aim of the study was to assess whether the Th1 and Th2 type cytokines, such as IL-2 and IL-10, affect ovarian carcinoma continuous cell line (SKOV-3) pro-inflammatory activation.Material and methodsSKOV-3 ovarian cells and peripheral blood mononuclear cells (PBMCs) were stimulated by IL-2 and IL-10. Additionally, SKOV-3 ovarian cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…In addition, several studies have demonstrated that the tumor cell line SKOV3 in the presence of PBMC causes the production of high concentration of IL-6 released by both SKOV3 cell line and PBMC. They also indicate that the interaction of these two types of cells provokes greater IL-6 production [48,58].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, several studies have demonstrated that the tumor cell line SKOV3 in the presence of PBMC causes the production of high concentration of IL-6 released by both SKOV3 cell line and PBMC. They also indicate that the interaction of these two types of cells provokes greater IL-6 production [48,58].…”
Section: Discussionmentioning
confidence: 93%
“…preterm labor, preeclampsia, fetal Down could be the aggressive biological nature of ovarian cancer whereby high levels of S1P produced by the tumor promote cell proliferation and cell transformation as well as survival of abnormal cells, neoangiogenesis and inhibition of pro-apoptotic processes. Currently, researchers are searching for useful markers in the advanced diagnosis of ovarian cancer [33,34]. Angiogenesis plays a crucial role in the tumor transformation, invasion and spread of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of T‐helper (Th) cells represents S. schenckii adaptive immunity which involves Th1‐type cytokine response in the early stage of the inflammatory reaction, while an elevated Th2‐type cytokine response promotes fungal infections in the late stage. Pro‐inflammatory cytokines can mediate the Th1‐type response with IL‐1 and TNF‐a 11 . The Th2‐type response is mainly characterized by the subsequent anti‐inflammatory cytokines IL‐4 and IL‐10.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines can mediate the Th1-type response with IL-1 and TNF-a. 11 The Th2-type response is mainly characterized by the…”
mentioning
confidence: 99%